How to diagnose and fix everything electronic - Geier, Michael (Michael Jay) (2016)
"A fully revised guide to electronics troubleshooting and repair. Repair all kinds of electrical products, from modern digital gadgets to analog antiques, with help from this updated book. [This book, in it's second edition], offers expert insights, case studies, and step-by-step instruction from a lifelong electronics guru. Discover how to assemble your workbench, use the latest test equipment, zero in on and replace dead components, and handle reassembly. Instructions for specific devices, including stereos, MP3 players, digital cameras, flat-panel TVs, laptops, headsets, and mobile devices are also included in this do-it-yourself guide."--provided by publisher.